Handbook of Sex Trafficking Feminist Transnational Perspectives (Springer International Publishing, 2018)
This definitive reference assembles the current knowledge base on the scope and phenomena of sex trafficking as well as best practices for treatment of its survivors. A global feminist framework reflects a profound understanding of the entrenched social inequities and ongoing world events that fuel trafficking, including in its lesser-known forms. Empirically sound insights shed salient light on who buyers and traffickers are, why some survivors become victimizers, and the experiences of victim subpopulations (men, boys, refugees, sexual minorities), as well as emerging trends in prevention and protection, resilience and rehabilitation. These powerful dispatches also challenge readers to consider complex questions found at the intersections of gender, race, socioeconomic status, and politics. A sampling of topics in the Handbook: · An organizational systems view of sex trafficking. · Vulnerability factors when women and girls are trafficked. · Men, boys, and LGBTQ: invisible victims of human trafficking. · Organized crime, gangs, and trafficking. · Human trafficking prevention efforts for kids (NEST). · Treating victims of human trafficking: core therapeutic tasks. · From Trafficked to Safe House (C-SAFE). The Handbook of Sex Trafficking will interest a wide professional audience, particularly mental health workers, legal professionals, and researchers in these and related fields. Public health and law enforcement professionals will also find it an important resource. .